Gambaran Nyeri Pasien Terpasang Ventilator Mekanik - Lestari, Nindi Vika; Rachmawati, Dewi; Sepdianto, Tri Cahyo (Jurnal Keperawatan Malang, 2024)
Background: The installation of a ventilator is a stressor that can cause discomfort and anxiety, potentially leading to complications and having serious impacts on the patient's condition. Objective: To determine the pain scale in patients with mechanical ventilators using the CPOT. Method: The design is descriptive, involving a sample of 30 individuals who meet the criteria of being ventilator-dependent on day 1 and classified as priority 1 critical patients. The sample was taken using an accidental sampling technique. The instrument used is the CPOT pain scale, which consists of four indicators: facial expressions, body movements, muscle tension, and compliance with the ventilator and vocalization (for non-intubated patients). Result: The research results showed that 60% of respondents experienced mild pain, 26.6% experienced moderate pain, and 13.3% experienced severe pain. These differences in pain levels are due to the varying interventions provided to the patients, which impacted physiological responses in the form of vital signs. Implication: It is recommended for nurses to identify the pain scale in patients attached to ventilators and provide psychotherapy to reduce pain so that patients can avoid complications.